Fast mode decision for scalable video coding over wireless network - Maarif, Haris Al Qodri; Gunawan, Teddy Surya; Priantoro, Akhmad Unggul (2010)
The scalable video coding H.264/SVC is the video coding standard which is an extension of H.264/AVC. Because of its scalability, H.264/SVC has gained a great interest in video transmission. Partial bit stream can be transmitted and decoded by the H.264/SVC in order to provide quality in lower temporal or spatial resolutions or reduced fidelity while retaining a reconstruction quality that is high relative to the rate of the partial bit streams. Hence, H.264/SVC provides functionalities such as graceful degradation in lossy transmission environments, i.e. wireless networks, as well as bit rate format, and power adaptation. This paper deals with the Medium-Grain SNR Scalability (MGS) scheme and fast coding mode decision. The MGS scheme with two enhancement layers is applied for enhancing the streaming video quality. To perform an optimum mode decision, motion estimation is performed for all Macro Block (MB) modes, and the Rate Distortion (RD) costs are compared to identify an MB mode with the smallest RD cost. This increases computational complexity of H.264/SVC encoding. Therefore, fast mode decision algorithm scheme was implemented to speed up the encoding time. From the experiment, the fast mode decision was able to decrease the encoding process up to 30.22%.